High resolution water temperature data between January 1997 and December 2018 at the GEOMAR pier surface - Fabian Wolf; Karl Bumke; Sebastian Wahl; Frauke Nevoigt; Ute Hecht; Claas Hiebenthal; Christian Pansch (PANGAEA, 2020)
Data from 1997-2018 were logged every 8 minutes in the Inner Kiel Fjord (54°19 extquotesingle46.0"N; 10°08 extquotesingle58.3"E) in shallow waters (Hydrometeorological station: Fa. Driesen und Kern, Bad Bramstedt). Until 2013 the sensor was deployed floating at the surface, but due to settlements on the floating device, the actual depth is not perfectly certain. Therefore, in 2013 the sensor was mounted to a fixed depth of 1.8 m (below sealevel). If a value differed more than 1.0°C from the preceding and following value, the value was interpolated between the two adjacent values. If values were 2) constant for more than 4 hours, 2) missing within ± 8 min, and if 3) changes in values exceeded 0.7°C within 16 min, the values were set to NA. This holds true for the following times: 1999-05-21 21:20 - 1999-06-17 15:00, 2000-11-10 12:00 - 2000-11-18 10:00, 2001-01-06 12:20 - 2001-01-08 07:40, 2014-08-30 18:00 - 2014-09-19 16:20, 2015-01-07 14:40 - 2015-02-23 20:00, 2016-11-09 03:20 - 2016-12-04 03:20 - 2017-01-24 23:25 - 2017-01-25 12:00. Gaps larger than 3 days were filled with data (if available) obtained from sensors very close to the actual measuring site (SeapHOx, Scripps Research Institute San Diego 1m; or Hydrometeorological station, Fa. Driesen und Kern, Bad Bramstedt 1.5m): 2000-11-11 - 2000-11-17 (Hydrometeorological station), 2001-08-03 - 2001-08-28 (Hydrometeorological station), 2005-10-07 - 2005-10-17 (Hydrometeorological station), 2006-02-09 - 2006-02-22 (Hydrometeorological station), 2014-08-29 - 2014-09-18 (Hydrometeorological station), 2015-01-08 - 2015-02-24 (Hydrometeorological station), 2016-03-10 - 2016-03-13 (SeapHOx), 2016-06-03 - 2016-06-15 (SeapHOx), 2016-11-10 - 2016-12-05 (SeapHOx). Data from 1.5 m water depth were corrected by subtracting a systematic deviance of 0.3°C.